Reunited with the sheriff ebook - Calhoune, Belle (2013)
The Prodigal Returns After injuring her best friend in a car accident, Cassidy Blake decided to leave town permanently. But now that her mother's sick, she's back to make amends. Sheriff Tate Lynch doesn't want to forgive his former fiancée for his sister's injury or for breaking his heart. And he certainly doesn't want to admit he still has feelings for her. The community can see her commitment to the town as she helps rebuild a church destroyed in a storm. But Tate's afraid of history repeating itself, even though Cassidy's actions prove she's a different person. Could the last secret she harbors about the accident drive Tate away for good?